2006
DOI: 10.1002/humu.20258
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of mutations inmutmethylmalonic acidemia and identification of a common Hispanic mutation and haplotype

Abstract: Cobalamin nonresponsive methylmalonic acidemia (MMA, mut complementation class) results from mutations in the nuclear gene MUT, which codes for the mitochondrial enzyme methylmalonyl CoA mutase (MCM). To better elucidate the spectrum of mutations that cause MMA, the MUT gene was sequenced in 160 patients with mut MMA. Sequence analysis identified mutations in 96% of disease alleles. Mutations were found in all coding exons, but predominantly in exons 2, 3, 6, and 11. A total of 116 different mutations, 68 of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
110
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 32 publications
11
110
0
Order By: Relevance
“…Radioactive incorporation studies with the N2 strain showed that C. elegans incorporates 1-[ 14 C]-propionate from propionate into protein in amounts similar to those seen in human cells [11 +/− 4 nmols/mg/18 hrs] [30] (Figure 3). Furthermore, a robust stimulation of incorporation was observed when hydroxycobalamin (OH-Cbl) was added to the medium in excess.…”
Section: Resultsmentioning
confidence: 89%
“…Radioactive incorporation studies with the N2 strain showed that C. elegans incorporates 1-[ 14 C]-propionate from propionate into protein in amounts similar to those seen in human cells [11 +/− 4 nmols/mg/18 hrs] [30] (Figure 3). Furthermore, a robust stimulation of incorporation was observed when hydroxycobalamin (OH-Cbl) was added to the medium in excess.…”
Section: Resultsmentioning
confidence: 89%
“…Mutation p.R369H, on the other hand, may be of a double origin (haplotypes 2 and 5). The p.R369 codon contains a CpG dinucleotide, and p.R369H has been found in Turkish, Greek, Caucasian, Hispanic (Worgan et al 2006), and Korean (Jung et al 2005) populations.…”
Section: Resultsmentioning
confidence: 99%
“…To date, more than 100 disease-causing mutations in the human MUT gene have been reported (Ledley and Rosenblatt 1997;Acquaviva et al 2005;Martinez et al 2005), most of which seem to be unique or restricted to only a few pedigrees. However, there have been reports of specific mutations among various ethic groups, including p.G717V in blacks (Adjalla et al 1998), p.N219Y in Caucasians (Acquaviva et al 2001), and p.R108C in Hispanics (Worgan et al 2006). Ogasawara et al (1994b) reported a relatively high incidence of p.E117X in Japanese patients and, more recently, Kobayashi et al (2006) identified the plural occurrence of each of six mutations (p.L494X, p.R93H, p.E117X, p.R369H, p.G648D, and c.385 + 5G > A) in another Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…Splice site mutations, deletions, and insertions are relatively rare (Acquaviva et al, 2005;Worgan et al, 2006;Dündar et al, 2012). Most mutations have been found only once and are restricted to a single family, and there have been no mutation hotspots identified.…”
Section: Discussionmentioning
confidence: 99%